Women in business and management : gaining momentum : global report - Wirth, Linda (International Labour Office, 2015)
This report brings together available data and ILO statistics to provide a comprehensive, up to-date and global picture of women in the business world and in management positions. It highlights the business case for gender diversity and the obstacles women still face as well as ways to move ahead.